Evaluation of Internalization Green Economy Behavior at SMA Negeri 32 Jakarta - Azmi, Wildan; Nurjanah, Siti; Saptono, Ari (International Journal of Applied Research and Sustainable Sciences, 2024)
This study examines the implementation of green economy behavior at SMAN 32 Jakarta. Flooding in Indonesia, exacerbated by plastic waste, highlights the need for environmental awareness. Using qualitative research and SWOT analysis, data were collected through observation and interviews with eight informants. The study employs IFAS and EFAS matrices to evaluate strengths, weaknesses, opportunities, and threats. Findings reveal successful implementation of green practices, such as using tumblers and waste sorting, supported by curriculum integration and teacher supervision. The recommended strategy for improvement is the SO (Strengths-Opportunities) strategy, aiming to embed green economy behavior in students' daily lives. This strategy leverages the school's strengths and opportunities for maximum impact.